Tindak Tutur dalam Kaiwa Pada Buku Minna No Nihongo 2 - Ana Natalia (Vocational College of Diponegoro University, 2023)
Speech acts are very important in conveying information or opinions to others. The Japanese language has a distinctive feature in conveying opinions or information, this is done so as not to offend or hurt the feelings of the interlocutor. Speech acts are an interesting area of pragmatics to study. In expressing opinions, Japanese people always use various strategies with the aim of refining what they want to say so as not to offend their interlocutors. In this study, researchers want to examine what speech acts are contained in Kaiwa (conversation) used in the Minna no Nihongo 2 book. The method used is descriptive by describing the speech acts found according to expert opinion. The results of the study found that speech acts in Japanese have a very important role in Kaiwa (conversation). This is because Japanese people do not want to make someone / recipient of information feel bad about what they want to convey. So that in every conversation or providing information they always use speech acts both locution, illocution and perlocution.